Whole-Genome Sequencing for National Surveillance of Shigella flexneri - Chattaway, Marie A.; Greig, David R.; Gentle, Amy; Hartman, Hassan B.; Dallman, Timothy J.; Jenkins, Claire (Frontiers in Microbiology, 2017)
National surveillance of Shigella flexneri ensures the rapid detection of outbreaks to facilitate public health investigation and intervention strategies. In this study, we used whole genome sequencing (WGS) to type S. flexneri in order to detect linked cases and support epidemiological investigations. We prospectively analysed 330 isolates of S. flexneri received at the Gastrointestinal Bacteria Reference Unit at Public Health England between August 2015 and January 2016. Traditional phenotypic and WGS sub-typing methods were compared. PCR was carried out on isolates exhibiting phenotypic/genotypic discrepancies with respect to serotype. Phylogenetic relationships between isolates were analysed by WGS using single nucleotide polymorphism (SNP) typing to facilitate cluster detection. For 306/330 (93%) isolates there was concordance between serotype derived from the genome and phenotypic serology. Discrepant results between the phenotypic and genotypic tests were attributed to novel O-antigen synthesis/modification gene combinations or indels identified in O-antigen synthesis/modification genes rendering them dysfunctional. SNP typing identified 36 clusters of two isolates or more. WGS provided microbiological evidence of epidemiologically linked clusters and detected novel O-antigen synthesis/modification gene combinations associated with two outbreaks. WGS provided reliable and robust data for monitoring trends in the incidence of different serotypes over time. SNP typing can be used to facilitate outbreak investigations in real-time thereby informing surveillance strategies and providing the opportunities for implementing timely public health interventions.